Collections of sandflies (diptera:psychodidae) from mammal burrows in an area of cutaneous leishmaniasis in Campeche, México - Rebollar Téllez, Eduardo Alfonso; Andrade, Francisco; Fernández Salas, Ildefonso; Reyes Villanueva, Filiberto (1996)
Sand flies were caught from December 1993 to November 1994 in an endemic focus of cutaneous leishmaniasis in the state of Campeche, Mexico. A total of 566 sand flies of seven species were collected using emergence funnel-traps, at openings of several mammal burrows. The main species collected were Lutzomyia deleoni and Brumptomyia hamata. Population abundance was found bimodal with the first and higher peak from January to March. A small second peak was found from May to October.